Causality analytics among key factors for green economy practices: Implications for sustainable development goals - Karuppiah, Koppiahraj; Sankaranarayanan, Bathrinath; Ali, Syed Mithun; AlArjani, Ali; Mohamed, Abdullah (Frontiers in Environmental Science, 2022)
The green economy (GE) concept is believed to have the ability to turn natural resources into wealth in a sustainable manner. As a result, the GE concept is viewed a magic key in the attainment of sustainable development goals (SDGs). This study aims to identify and evaluate the critical factors in GE practices. Based on literature review and industrial interaction, five dimensions of critical factors namely, economic and market, technical and R&D, policy and regulation, networks and social capital, and public perceptions, with a total of twenty critical factors were identified and evaluated. Fermatean fuzzy system (FFS) based Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique has been used to evaluate the causality among the critical factors. Results reveal that win-win anticipations, commitment of key stakeholders, domestic market structure, cost of alternatives, and financial assistance are the top five critical factors in GE practices. Three critical factors are classified under the cause category, and the remaining seventeen critical factors come under the effect category. This study contributes to the literature on GE by revealing the causal interrelationship among the critical factors. This will guide industrial management to take appropriate actions in the implementation of GE practices.